Building Quality Student Writing: Application of Critical Review of Articles In Reputable Journals to Improve Students’ Ability to Compile Thesis Proposals - Agus Yudiawan; Nur Adzidzah (Journal of Quality Assurance in Islamic Education (JQAIE), 2023)
This study aims to determine the improvement of students' ability to compile thesis proposals after applying a critical review of reputable journal articles. The research method used a classroom action research model with two action cycles. The results showed a significant increase in students' ability to compile thesis proposals after applying a critical review of reputable journal articles. Before the action, the power of students to collect viable proposals was only 33% and could be increased to 78%. The conclusion is that the application of critical review can be used to improve students' ability to compile thesis proposals. Keywords: a critical review, student ability, thesis proposal.